Life-cycle cost models for green buildings : with optimal green star credits - Illankoon, I. M. Chethana S.; Tam, Vivian W. Y.; Le, Khoa N. (Butterworth-Heinemann, 2021)
Life-Cycle Cost Models for Green Buildings: With Optimal Green Star Credits illustrates the tools and methods for developing a life-cycle cost model that incorporates developer constraints while maximizing the number of credit points achieved. The book identifies the interdependencies among various credits in the Green Star environmental rating system. Afterwards, life-cycle cost is calculated by considering six main central business districts (CBDs) of Australia. The net present value (NPV) technique is used to calculate life-cycle costs. Further, a sensitivity analysis is also carried out for selected credits to identify the changes to life-cycle cost to the changes in discount rate. Once all the life-cycle cost data is calculated, this book illustrates the development of the proposed model using a Java application which allows users to evaluate each key criterion of green buildings separately. The book is designed to provide ample knowledge of the various options available to get green building certification and the further implications in-terms of life-cycle.